Computed tomography imaging for the characterisation of drugs with radiation density measurements and HU spectroscopy - Dominik A. Sieron; Moritz Steib; Dominik Suter; Verena C. Obmann; Adrian T. Huber; Lukas Ebner; Daniel Inderbitzin; Andreas Christe (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY